The scorpion toxin Bot IX is a potent member of the α‐like family and has a unique N‐terminal sequence extension. Issue 18 (1st September 2016) - Martin‐Eauclaire, Marie‐France; Salvatierra, Juan; Bosmans, Frank; Bougis, Pierre E.
Abstract : We report the detailed chemical, immunological and pharmacological characterization of the α‐toxin Bot IX from the Moroccan scorpion Buthus occitanus tunetanus venom. Bot IX, which consists of 70 amino acids, is a highly atypical toxin. It carries a unique N‐terminal sequence extension and is highly lethal in mice. Voltage clamp recordings on oocytes expressing rat Nav1.2 or insect BgNav1 reveal that, similar to other α‐like toxins, Bot IX inhibits fast inactivation of both variants. Moreover, Bot IX belongs to the same structural/immunological group as the α‐like toxin Bot I. Remarkably, radioiodinated Bot IX competes efficiently with the classical α‐toxin AaH II from Androctonus australis, and displays one of the highest affinities for Nav channels. Abstract :